Multifactorial analysis and experiments affecting the effect of fog droplet penetration in fruit tree canopies - Sun, Daozong; Huang, Xinghan; Hu, Junyutai; Jiang, Haoliang; Song, Shuran; Xue, Xiuyun (Frontiers in Plant Science, 2024)
This study examines the effects of canopy density, side wind speed, nozzle tilt angle, and droplet size on droplet penetration during plant protection spraying operations. Experiments in citrus orchards evaluated how side wind speed and nozzle tilt angle influence droplet penetration across various canopy densities. A Phase Doppler Analyzer (PDA) was used to assess droplet size variations under different nozzle tilt angles and side wind speeds. The data yielded a multiple linear regression equation (R² = 0.866), linking nozzle tilt angle and side wind speed with droplet size. Results showed that droplet size decreases with increasing nozzle tilt angle at a constant crosswind speed. Further experiments investigated the effects of droplet size and canopy leaf area density on droplet penetration. The spray tests involved three canopy leaf area densities, four wind speeds, and six nozzle tilt angles. Droplet deposition and canopy coverage were measured under various spraying parameters, with conventional operations (0° nozzle tilt and orthogonal wind speeds) as controls. The study found that adjusting nozzle tilt angle and wind speed enhances droplet penetration in different canopy structures. Optimal parameters varied with leaf area density (LAD): an 18° tilt angle and 3 m/s wind speed for a LAD of 5.94 m² /m³ , a 45° tilt angle and 2 m/s wind speed for a LAD of 8.47 m² /m³ , and a 36° tilt angle and 3 m/s wind speed for a LAD of 11.12 m² /m³ . At 2 m/s, droplet deposition followed a downward parabolic trend with changes in nozzle tilt angle, whereas at 3 m/s, deposition followed an upward parabolic trend. At a side wind speed of 3 m/s, droplet deposition remained unchanged with nozzle tilt angle but decreased with increasing canopy density. Nonlinear regression analysis indicated that leaf area density had a greater impact on deposition differences than droplet size, with droplet penetration decreasing as leaf area density increased. This study provides a reference for enhancing fog droplet penetration techniques in plant protection operations.